2017
DOI: 10.1039/c7ra02506h
|View full text |Cite
|
Sign up to set email alerts
|

Safer-by-design hybrid nanostructures: an alternative to conventional titanium dioxide UV filters in skin care products

Abstract: Experimental synthesis of TiO2 nanoparticles via safer-by-design approach to minimize their exposure risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 60 publications
1
11
0
Order By: Relevance
“…Oza first demonstrated that microcrystalline cellulose was able to form a network around oil droplets . Since that publication, many nanocelluloses stabilized emulsions have been reported with the various types of nanocelluloses; nanofibrillated celluloses, , cellulose nanocrystals, and bacterial nanocellulose. , Nanocellulosic materials can also be hydrophobized to produce water-in-oil emulsions , and double emulsions, , or modified for functional emulsions. Such particle stabilized emulsions refer to the so-called Pickering emulsions that form surfactant-free, highly stable emulsions armored by a layer of solid particles. If the mechanism of adsorption is not fully elucidated, several points are already clearly established.…”
Section: Introductionmentioning
confidence: 99%
“…Oza first demonstrated that microcrystalline cellulose was able to form a network around oil droplets . Since that publication, many nanocelluloses stabilized emulsions have been reported with the various types of nanocelluloses; nanofibrillated celluloses, , cellulose nanocrystals, and bacterial nanocellulose. , Nanocellulosic materials can also be hydrophobized to produce water-in-oil emulsions , and double emulsions, , or modified for functional emulsions. Such particle stabilized emulsions refer to the so-called Pickering emulsions that form surfactant-free, highly stable emulsions armored by a layer of solid particles. If the mechanism of adsorption is not fully elucidated, several points are already clearly established.…”
Section: Introductionmentioning
confidence: 99%
“…From a sample of six sunscreens, rutile nTiO 2 was present in three sunscreens, while the combination of rutile and anatase forms of nTiO 2 was in one sunscreen [10,22,69]. Overall, most studies demonstrate that rutile nTiO 2 is the most widely used form [10,58,59,[70][71][72][73]. Rutile nTiO 2 has also been reported in paints [10] and cotton fabrics [61].…”
Section: Titanium Dioxide Nanoparticles (Ntio 2 )mentioning
confidence: 97%
“…Other than that, the physical and chemical properties of these materials can be tuned to the desired direction. The diverse nature of softness, flexibility, and functionality of the organic part in a hybrid system interlinked with the hard, rigid, and thermally stable inorganic components exponentially raises their potential in developing advanced functional materials 11 . In support of this, few works have been reported related to developing hybrid materials that remarkably utilize ZnO, and TiO 2 , as inorganic counterparts along with polymers as organic parts for UV‐blocking applications.…”
Section: Introductionmentioning
confidence: 99%